Zataria multiflora extract reverses lipopolysaccharide-induced anxiety and depression behaviors in rats - Zohreh Arab; Mahmoud Hosseini; Fatemeh Mashayekhi; Akbar Anaeigoudari (Mashhad University of Medical Sciences, 2019)
Objective: Stressors have an important role in sickness behaviors. We checked the effect of Zataria multiflora (ZM) extract against lipopolysaccharide (LPS)-induced anxiety and depression behaviors in rats. Material and Methods: Rats were distributed in the following groups (n=10): Control, LPS (1 mg/kg), LPS-ZM50, LPS-ZM100 and LPS-ZM200. LPS was syringed intraperitoneally (ip) 2 hr before performing behavioral tests. LPS-ZM groups were treated with 50, 100 and 200 mg/kg (ip) of ZM extract 30 min before LPS administration. Open field (OF), elevated plus maze (EPM) and forced swimming (FS) tests were done. White blood cell (WBC) was counted in all groups. Results: In OF, pretreatment with ZM extract augmented the number of lines crossed and traveled distance in central and peripheral areas. The rats treated with ZM extract spent more time in the central zone and less time in the peripheral area compared to the LPS group. In EPM, the number of entries into the open and closed arms and stop time in the open arms in LPS-ZM groups were higher than the LPS group. The stop time in the closed arms of ZM-LPS groups was less than the LPS group. In FS test, swimming and climbing time in groups treated with ZM extract was more than the LPS group while their immobility time was less. WBC count in the LPS-ZM100 and LPS-ZM200 was lower than that of the LPS group.   Conclusion: Based on the results, pretreatment with ZM extract restituted anxiety and depression caused by LPS in rats. This effect of ZM was associated with amelioration of LPS-promoted inflammation.